Cutaneous wound healing in aged, high fat diet-induced obese female or male C57BL/6 mice - Kopcewicz, Marta (Aging (Albany NY), 2020)
Since there are limited studies analyzing the impact of age, sex and obesity on cutaneous repair, the current study evaluated excisional skin wound healing as a function of age, sex and diet in C57BL/6 mice subjected to either low (LFD) or high (HFD) fat diet. Older mice accumulated increased body fat relative to younger mice under HFD. Skin wound healing at particular stages was affected by age in the aspect of Tgfβ-1, MCP-1, Mmp-9 and Mmp-13 expression. The most profound, cumulative effect was observed for the combination of two parameters: age and sex. While skin of younger males displayed extremely high collagen 1 and collagen 3 expression, younger females showed exceptionally high Mmp-13 expression at day 3 and 7 after injury. Diet as a single variable modified the thickness of dermis due to increased dermal White Adipose Tissue (dWAT) accumulation in mice fed HFD. The combination of age and diet affected the re-epithelialization and inflammatory response of injured skin. Overall, our data indicate that age has the most fundamental impact although all components (age, sex and diet) contribute to skin repair.